Dysmenorrhea in adolescents requires careful investigation of endometriosis—an analysis of early menstrual experiences in a large case-control study - El-Hadad, Samia; Lässer, Daksha; Sachs, Maike-Katja; Schwartz, Alexandra Sabrina Kohl; Haeberlin, Felix; von Orelli, Stephanie; Eberhard, Markus; Leeners, Brigitte (Frontiers in Reproductive Health, 2023)
Recent evidence shows that endometriosis, a significant cause of infertility, may already present in adolescents. Dysmenorrhea, often leading to school absences, is a key symptom of the maturing menstrual cycle but also of endometriosis. However, it is often perceived as "normal" and left untreated. In adolescents, laparoscopy, the standard procedure to diagnose endometriosis, is performed particularly cautiously. To improve reproductive health in adolescents, we evaluate associations between early menstrual experiences and endometriosis.Methods: Retrospective data on early menstrual experiences from 563 women with surgically/histologically verified endometriosis and from 563 age-matched controls were compared. Study participants were recruited in Switzerland, Germany, and Austria. Information on menstrual experiences was collected via a structured questionnaire. Results: The bivariate analysis showed that early menarche (p=0.004), dysmenorrhea and negative memories of menarche (p<0.001) were significantly associated with a diagnosis of endometriosis. After controlling for confounders in bivariate regression analysis occurrence of dysmenorrhea (p=<0.001, OR 5,74, 95% CI 3.82-7.22) especially with onset > 3 years after menarche ((p=<0.001, OR 3.42, 95% CI 2.09-5.64) remained statistically significant predictors for diagnosis of endometriosis. Dysmenorrhea in mothers and mothers' perceived attitude towards menstruation were not associated with the occurrence of Endometriosis. Conclusions: Dysmenorrhea and onset of dysmenorrhea at menarche or several years after it are strongly associated with the development of endometriosis. As mothers perceived attitudes towards menstruation show no significant association with their daughters' experiences, physical symptoms accompanying menarche and menstrual period pain in adolescents seem to be very reliable predictors in diagnosis of endometriosis. Therefore, dysmenorrhea in adolescents requires careful investigation of possible endometriosis, especially if it does not respond to medical management.